The level of green innovation adoption among construction firms in Scotland - Hashim, Rushanim (2018)
The construction industry plays a vital role in meeting the needs of society and enhancing the quality of life.It contributes to a better standard of living for people and increases the economic output of countries all over the world. However, its activities are considered as making a major contribution to environmental problems.From emitting greenhouse gas to contributing waste, construction is not an environmentally-friendly activity.These conflicting issues have pressured the industry to intensify its effort and move towards sustainable construction.As the government in United Kingdom has set target towards sustainability achievement by 2050, it is necessary for the construction industry to play its role to protect the environment by engaging in environmental-related practices.The aim of this study, therefore, to examine the level of green innovation adoption by Scottish construction firms.Based on the results of descriptive analysis, more than half of the participated Scottish construction firms have adopted various types of green technical and green process during construction.Green administrative practices, however, were less adopted by the construction firms with relatively small percentages. The implications for theories of innovation adoption and knowledge enhancement associated with environmentally-friendly practices is also discussed.